“Modelo de Gestión del Talento Humano y su incidencia en la toma de decisiones de la Cooperativa de transportes Patria cantón Riobamba, período 2014.” - Oña Jara, Paola Carina (2016)
The subject of this research is “management model of human talent and its impact on decision making of the cooperative Patria Transport Riobamba Canton, 2014 period ", the thesis developed it into 5 chapters, the first chapter identifies the problematic situation in relation to the management of the Coopertiva of Trasportes Patria, the second chapter presents the theoretical foundation, in relation to the administrative components, with an emphasis on strategic management, the third chapter shows the type of research, demarcándola as exploratory, descriptive and explanatory in relation to its type, in the design of research is documentary and field; documentary because documents like schedules are investigated, and field since surveys were conducted to identify processes and collect information concerning the elements of the administrative process relating to business management and decision-making, the population for this research it is the staff of the Cooperative country, in this case does not show will be used as the entire population was applied. Within the analysis, it started by the external, and within it the identification of the impact of economic external, social, environmental and technological variables, which has classified them as opportunities or threats, regarding the internal analysis, began by business components in relation to the administrative process, ie planning, organization, management and control, information obtained through a survey and through direct observation, as to all areas of the cooperative in 2014 and SWOT information summarizing all findings was performed. So it is concluded that inadequate corporate governance has a negative impact on decision making, and a strategic plan aimed at improving management and decision making was proposed.